(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe the clinical and paraclinical characteristics of patients undergoing laparoscopic perforation closure for gastric perforation at Nguyen Tri Phuong Hospital. Materials and Methods: A retrospective case series study was conducted, collecting data from 62 patients with gastric perforation admitted between January and December 2018. Clinical and paraclinical characteristics were analyzed using Stata statistical software. Results: Among 62 patients, the mean age was 50.0 ± 16.6 years, with males predominating (79%). Common presenting symptoms included abdominal pain (100%), vomiting (53.2%), abdominal guarding (66.1%), and board-like rigidity (43.5%). Erect abdominal X-ray detected subdiaphragmatic free air in 51.6% of cases, while CT scan revealed intra-abdominal fluid in 54.8% and free air in 53.2%. The median perforation size was 6.3 mm, with the duodenal bulb being the most common perforation site (52.9%). Conclusion: The findings indicate that laparoscopic surgery is an effective intervention for gastric perforation, particularly in patients with small perforations. However, careful assessment of perforation size and inflammation severity is crucial to minimize adverse outcomes. A multimodal approach to diagnosis and treatment plays a key role in optimizing patient outcomes.